A robust integrator algorithm with genetic based fuzzy controller feedback for direct vector control - Akin, E; Kaya, M; Karakose, M (Pergamon-Elsevier Science Ltd, 2003)
The voltage model used for direct vector control has in the flux calculation process an open integration problem. which is generally solved with a feedback loot), in this paper. a new design method is developed for the feedback loop of the integrator. The method. as apart from standards in the literature. uses a fuzzy controller. Fuzzy controllers are knowledge-hased systems that include fuzzy rules and fuzzy membership functions to incorporate human knowledge into their knowledge base. The determination of these rules and membership functions is one the key problems when designing fuzzy controllers. and is generally affected by subjective decisions. In this study, a fuzzy controller with rules and membership functions determined by genetic algorithms (GAs) in this study is designed and tested on various motors of different power ratings. The proposed method is simulated by using MATLAB/SIMULINK and implemented on an experimental processor. system using a TMS320C31 digital Signal (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: vector control; flux estimation; fuzzy controller; genetic algorithm; induction motor